Modeling and simulation of a 2-seated helicopter in longitudinal motion [electronic resource] - 389652 Ho, Joo Cong (2008)
Project Paper (Sarjana Muda Kejuruteraan Mekanikal) - Universiti Teknologi Malaysia, 2008